Quality of Nursing Work Life (QNWL): A Scoping Review of Concepts, Determinants, and Outcomes - Lilis Suryani (STIKep PPNI Jawa Barat, 2026)
Background: Quality of Nursing Work Life (QNWL) is increasingly recognized as a critical determinant of nurses’ well-being, retention, and performance. However, heterogeneity in conceptualization, measurement, and methodological approaches limits comparability and practical application. Objective: This scoping review aimed to map and synthesize contemporary evidence on QNWL, focusing on its definitions, measurement instruments, determinants, outcomes, and research gaps. Methods: A scoping review was conducted following the Joanna Briggs Institute (JBI) methodological framework and reported in accordance with PRISMA-ScR. Searches were performed in PubMed/MEDLINE, Scopus, Web of Science, CINAHL, and PsycINFO for studies published in English between January 2019 and February 2025. Google Scholar (first 200 results, sorted by relevance) and reference list screening were used as supplementary sources. Eligibility was defined using the Population–Concept–Context (PCC) framework. Data were charted descriptively and synthesized narratively. Methodological appraisal using JBI tools was conducted to describe study quality, not to exclude evidence. Results: Fifteen studies met inclusion criteria, encompassing cross-sectional surveys, psychometric validation studies, and contextual reviews from diverse geographic settings. The Brooks Quality of Nursing Work Life scale and the Work-Related Quality of Life instrument were most frequently used, reflecting continued conceptual heterogeneity. Key determinants of QNWL included leadership quality, workload, staffing adequacy, and organizational climate. Higher QNWL was consistently associated with greater job satisfaction, organizational commitment, and intention to stay, whereas lower QNWL was linked to burnout and turnover intention. Most studies were cross-sectional, limiting causal inference. Conclusions: QNWL is a multidimensional, context-sensitive construct shaped primarily by organizational and leadership factors. While evidence consistently links QNWL with workforce stability and well-being, methodological limitations and conceptual variability remain. Future research should prioritize longitudinal and interventional designs, standardized measurement, and broader contextual coverage to inform sustainable nursing workforce policies